Comparison of two doses and two routes of administration of misoprostol after pre-treatment with mifepristone for early pregnancy termination - Marions Lena; Piaggio Gilda; von Hertzen Helena (Reproductive Health, 2008)
Abstract Background It is not known whether a 400 μg dose of misoprostol has a similar efficacy as an 800 μg dose when administered sublingually or vaginally 24 hours after 200 mg mifepristone. Methods It is proposed to undertake a placebo-controlled, randomized, non-inferiority trial (3% margin of equivalence) of the two misoprostol doses when administered sublingually or vaginally using factorial design. A total of 3008 pregnant women (< 63 days of gestational age) who request legal termination of pregnancy will be recruited for the trial at 16 clinics in ten countries providing abortion services. Eligible women willing to join the study will be allocated randomly to one of the four treatment groups within each centre. Women in all treatment groups will first receive 200 mg mifepristone, followed 24 hours later by either 400 μg or 800 μg misoprostol, administered either sublingually or vaginally. The dose and route of administration of misoprostol will be blinded to women, each woman receiving four tablets vaginally and four tablets sublingually, two or four of which are 200 μg tablets of misoprostol and the rest are placebo tablets. The four treatment regimens will be compared in terms of: (i) their efficacy to induce complete abortion; (ii) induction-to-abortion interval when possible; (iii) the frequency of side effects; and (iv) women's perceptions. The initial judgment of the outcome of treatment is made at the follow-up visit on day 15 of the study and the final assessment four weeks later. It is estimated that the clinical phase will require 12–14 months for data collection. To compare the two routes and two doses, relative risks (RR) of failure to achieve a complete abortion and failure to terminate pregnancy and the two-sided 95% CIs will be calculated by standard methods, as well as risk differences and two-sided 95% CIs. The latter will be used to test the non-inferiority hypotheses (at 2.5% level of significance) for achieving complete abortion. The factorial structure will be taken into account in the analysis after testing the interaction. Trial registration ISRCTN87811512